ANALISIS YURIDIS PERTIMBANGAN HUKUM PUTUSAN PENGADILAN AGAMA PURBALINGGA NOMOR 1720/PDT. G/2013/ PA. PBG TENTANG PENYELESAIAN GUGATAN WANPRESTASI DALAM PEMBIAYAAN AKAD MURABAHAH - Muhammad Fadhly ASE (IAIN Batusangkar, 2015)
This research was aimed at analyzing the legal considerations juridical verdict at religious court of Purbalingga case number 1720/Pdt. G/2013/PA. Pbg. The results revealed that in this decision, the judges had attempted to meet the judicial procedure and the principle of legal certainty in resolving the default of murabahah financing contract. In general the consideration and application of the law used by judges in case number 1720/Pdt. G/ 2013/PA. Pbg. was right and true, but there were some things less considered by the judges in the decision.Keywords: Legal Consideration, Juridical Verdict, Religious Court, Default, Murabahah